The effect of leaflet-based education and simulation of first-aid in accidents (P3K) on the knowledge and skills of tourism workers in Indonesia - Adelia Permatasari; Anita Sulistyorini; Supriyadi Supriyadi; Nurnaningsih Herya Ulfah (Public Health and Occupational Safety Journal, 2025)
Background: Law Number 1 of 1970 concerning Occupational Safety requires all sectors, including tourism, to implement Occupational Safety and Health (K3). Taman Dolan Batu City, as a tourist destination, has a risk of work accidents, so it needs mitigation efforts through First Aid for Accidents (P3K). Objectives: This study aims to analyze the effect of leaflet-based education and simulation on workers' knowledge and first aid skills. Methods: The research design used a quasi-experiment conducted with a sample of 16 people divided into two different intervention groups. This study uses questionnaire instruments and observation sheets that have been proven valid and reliable through statistical tests (Pearson, Aiken's V, and Cronbach Alpha) and experts' validation of leaflet educational media. Data analysis used Wilcoxon Signed Rank, and Mann-Whitney U tests with a significance level of 0.05. Results: The results of hypothesis testing showed that both educational methods significantly improved workers' knowledge and skills (p<0.05). The combined intervention of leaflet and simulation proved more effective than the single method. Conclusions: Leaflet-based education and simulation together are more effective in improving the knowledge and skills of first aid workers at Dolan Park. Researchers recommend that managers routinely hold K3-related training to reduce the risk of workplace accidents. Future research is recommended to involve a larger sample and evaluate the long-term effectiveness of the intervention provided.